Digital cultures, lived stories and virtual reality - Maschio, Thomas (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book focuses on the meaning and experience of digital practice, emerging from work in the world of business and drawing on recent anthropological thinking on digital culture. Tom Maschio suggests that the digital is a space of a new 'story culture' and considers the lived experience of new technologies. The chapters cover: storytelling in journalism and business with the new technology of virtual reality, the emerging meanings of social media and community building in the digital space, the uses and meanings of visual imagery online, and the cultural meanings of smartphone technology use and the 'mobile life'. The book incorporates ideas from humanistic anthropology and phenomenology in order to bring business problems into alignment with human concerns and desires, and to show the application of anthropological ideas to real-world issues. As well as anthropologists, the book will be valuable to business students and professionals interested in the digital realm"--
Keywords: Information technology -- Social aspects; Digital media -- Social aspects; Virtual reality -- Social aspects; Internet -- Social aspects; SOCIAL SCIENCE / Anthropology / General; SOCIAL SCIENCE / Anthropology / Cultural